Film Dokumenter sebagai Media Peningkatan Kualitas Pendidikan Karakter dan Literasi Budaya di Perguruan Tinggi - payuyasa, payuyasa; Ida Bagus Hari Kayana Putra; Gangga Lawranta; Ni Nyoman Ayu Suciartini (Jurnal Penjaminan Mutu, 2025)
The artistic journey in Bali has been ongoing for a long time. Various artistic activities taking place today are the result of a long journey of devotion by artists to art itself. One of the few art maestros now in his twilight years, with an extraordinary legacy, is I Ketut Muji. Based on initial research conducted by the author on maestro I Ketut Muji, there are many values and lessons that must be passed down to the artists in Bali. I Ketut Muji is a dance maestro with a strong character and style that, to this day, has not been inherited by anyone. The legacy of I Ketut Muji, as presented in this documentary film, is rich in educational and cultural literacy values, especially in preserving the traditional art of Balinese dance. The movements conveyed by the maestro in his dances embody educational philosophies that can serve as inspiration for pursuing education in its truest and most vibrant form. The primary goal of documenting the maestro's knowledge in film is to preserve and develop the values, ethics, and intellectual journey of I Ketut Muji for future generations, particularly for the artists in Bali. Featuring maestro I Ketut Muji in his twilight years in a documentary is of utmost importance. This film is produced to convey the knowledge, attitudes, and life perspectives of I Ketut Muji regarding dance and dancers to current and future Balinese dance practitioners. Therefore, "The Legacy of Maestro I Ketut Muji in a Documentary Portrait" is essential to be continued as a work beneficial to the broader community. The creation of this documentary film is supported by research employing a phenomenological approach to interpret phenomena and explore the knowledge of Maestro I Ketut Muji. The data collection methods used include observation and interviews. The design of the proposed creation is a portrait documentary film with an expository approach. The stages in producing this documentary film include three main points: pre-production, production, and post-production. The results of this research show that the documentary film "The Legacy of Maestro I Ketut Muji" provides insights related to character education and cultural literacy. Values such as honesty, independence, perseverance, love for culture, patriotism, resilience, and courage are exemplary traits of the maestro. The cultural literacy education in this documentary relates to the history of dance traditions, the rules or standards for performing Balinese dance, costumes, the religious functions of Balinese dance, and the principles of dedication to traditional arts.